1993
DOI: 10.5014/ajot.47.6.535
|View full text |Cite
|
Sign up to set email alerts
|

Student Coping Strategies and Perceptions of Fieldwork

Abstract: A questionnaire, the revised Ways of Coping Checklist, was sent to all professional (entry-level) graduate students in the United States in one academic year during their second fieldwork level II experience to determine what coping strategies they used during their fieldwork experience. Information was also gathered regarding their perceptions of this clinical experience. Responses from 101 students showed that they used Problem-Focused and Seeks Social Support strategies more than Wishful Thinking, Blamed Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
1
10
0
5
Order By: Relevance
“…The fact that the OT students rated so many items as highly important is noteworthy. These results have some similarities to the findings of a study of OT Level II FW students' coping strategies that was conducted by Mitchell and Kampfe (1993). This study indicated that a common stressor among OT students is the perception that they should not make mistakes in knowledge or skill performance while on FW.…”
Section: Discussionsupporting
confidence: 79%
“…The fact that the OT students rated so many items as highly important is noteworthy. These results have some similarities to the findings of a study of OT Level II FW students' coping strategies that was conducted by Mitchell and Kampfe (1993). This study indicated that a common stressor among OT students is the perception that they should not make mistakes in knowledge or skill performance while on FW.…”
Section: Discussionsupporting
confidence: 79%
“…Mitchell and Kampfe (1993) also found that students used peer support as a method of coping with stress on fieldwork. This was especially true for those for whom this was a new type of placement:…”
Section: Discussionmentioning
confidence: 95%
“…Most articles were program descriptions and were not focused on an examination of practices from a research perspective. These articles describe models of practice (Hengel & Romeo, 1995;Herge & Milbourne, 1999;Farrow, 2000;Jung, 2002;Nolinske, 1995;Mackenzie, 2002;Sabari, 1985;Schemm & Bross, 1995), ways that students cope with the fleldwork experience (Evenson, Barnes, & Cohn, 2002;Mitchell & Kampfe, 1993), or provide strategies to help supervisors address student needs (Ilott, 1995, Mackenzie, 2001. Bondoc (2005), searching for research in occupational therapy educational practices, found "a scant amount of research with low levels of methodological quality" (p. 2).…”
Section: Occupational Therapymentioning
confidence: 99%